2011
DOI: 10.1016/j.diamond.2011.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ion beam implantation of diamond

Abstract: Keywords: Diamond Focused ion beam FIB EBSD EELS TEM STEM Ion implantation Amorphous carbon Diamond like carbonThe interaction between diamond and a 30 kV Ga + focused ion beam, has been studied. Electron backscattered diffraction identified the critical dose for amorphisation of the diamond surface at 2 × 10 14 Ga + /cm 2 . Scanning transmission electron microscopy identified a 35 nm amorphous carbon layer which, at higher doses, can swell up to 31% its original volume and accommodate a significant quantity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 17 publications
(21 reference statements)
4
33
0
Order By: Relevance
“…Most recently, few attempts have been made to study the ion-induced amorphization of diamond. McKenzie et al [22] has recently reported that the near-surface microstructure varies with the increase of ion dose and the critical dose for the amorphization of the diamond surface is 2.0 × 10 14 ions/cm amorphlization. For another study of 30 keV Ga + sputtered nanocrystalline diamond films, the thickness of the damage layer was found to grow with the ion dose and achieved an equilibrium value of 44 nm [18].…”
Section: The Dynamic Damage Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, few attempts have been made to study the ion-induced amorphization of diamond. McKenzie et al [22] has recently reported that the near-surface microstructure varies with the increase of ion dose and the critical dose for the amorphization of the diamond surface is 2.0 × 10 14 ions/cm amorphlization. For another study of 30 keV Ga + sputtered nanocrystalline diamond films, the thickness of the damage layer was found to grow with the ion dose and achieved an equilibrium value of 44 nm [18].…”
Section: The Dynamic Damage Processmentioning
confidence: 99%
“…Typically, Gnaser et al [18] has reported a fluence-dependent evolution of the implanted Ga concentration in nanocrystalline diamond films by SIMS. Rubanov et al [21] and McKenzie et al [22] investigated the ion fluence-dependent amorphization of diamond substrate under 30 keV Ga + FIB milling. These experiments show the existence of atomic damaged layer in chemical vapour deposition (CVD) or doped diamond materials under high energy irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mckenzie et al [19] reported that the near surface microstructure of a single crystal natural conductive diamond varies with the increase of ion dose, and the critical dose for the amorphization of the diamond substrate (thickness of 35 nm) is 2.0 × 10 14 ions/cm 2 . Additionally, Gnaser and co-workers [16] has reported a fluence-dependent evolution of the implanted Ga concentration in nanocrystalline diamond films by SIMS.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a variety of experimental techniques including Raman spectroscopy [17], transmission electron microscope (TEM) [18,19], and secondary ion mass spectrometry (SIMS) [16] have been used to study the ion-induced damage in diamond. Admas et al [9] used TEM to study the amorphous carbon layer in single crystal diamond tool created by FIB milling and a larger amorphous layer was found when a small local incident angle of ion beam applied.…”
Section: Introductionmentioning
confidence: 99%